Numerical simulation of ultrasonic speckle field reflected from a Gaussian interface. (1st January 2014) - Zheng, Weihua; Jia, Hu
Due to the received ultrasonic speckle is carried out point by point, the whole process is influenced by noise, and there is bigger measuring error. For this reason, the computational simulation of ultrasonic speckle field was proposed. The simulation speckle field produced by the Gaussian random surfaces on the far field, the sound intensity distribution and phase distribution were also obtained; the phase singularity exists in the speckle field and the phase distribution similar to swirl around singular points. Simultaneously, the ultrasonic speckle field receiving experimental system is established. By contrast, the intensity distribution of speckle field is generated by the simulation and that obtained experimentally is similar, but the intensity of simulative ultrasonic speckle field is greater, the highlighted speckles that carry more useful information is more, dark spot is less, and that is more conducive to research and analysis.